(untitled) (Journal of the Spanish Institute for Strategic Studies, 2013)
This paper analyses some of the ambiguities of the legal regulation of theUN Charter concerning the use of force, which have received particularattention during the last decade. Firstly, the new problems arising from theinterpretation and application of the right of self-defence. In particular, theadmissibility of self-defence against potential threats or in response to majorterrorist attacks. Secondly, the debate about the emergency of a collectiveresponsibility to protect the civil population against genocide, war crimes,ethnic cleansing and crimes against humanity and its potential consecrationas a rule of law.